EVALUASI MANAJEMEN ZAKAT INFAQ DAN SEDEKAH DI LEMBAGA AMIL ZAKAT INFAK DAN SEDEKAH MUHAMMADIYAH KABUPATEN BOGOR (LAZISMU) - Yani, Ahmad; Waki , Ahmad; Misno (Institut Agama Islam Sahid Bogor, 2024)
This study aims to evaluate the management of Lazismu Bogor Regency in managing zakat, infaq and alms and to find out and evaluate the performance of Lazismu Bogor Regency, and to increase the philanthropy of the people of Bogor Regency in paying zakat, infaq and alms. The type of research used in this study is descriptive qualitative, namely digging up information in depth by conducting direct interviews to the field. While the instrument approach method is by using strategic management approach instruments, philanthropic theory and sharia management. The place of this research is Lazismu, Bogor Regency. The results of this study indicate that Lazismu Bogor Regency in managing zakat, infaq and alms is quite good, consisting of planning strategies, promotion strategies, collection strategies as well as distribution and evaluation strategies. The increase in philanthropic interest in the Bogor Regency community from 2017 to 2019 has continuously increased the number of donors. However, there are a number of things that must be evaluated, including the absence of HR focused on being permanent employees at Lazismu Bogor Regency, the absence of a special Lazismu Bogor Regency office and the presence of several administrators who hold concurrent positions at Muhammadiyah Business Charities, Agencies and other Institutions.